Ulvan and Ulva oligosaccharides: a systematic review of structure, preparation, biological activities and applications - Chen Li; Tiancheng Tang; Yuguang Du; Ling Jiang; Zhong Yao; Limin Ning; Benwei Zhu (Bioresources and Bioprocessing, 2023)
Abstract Ulva is one of the main green algae causing green tide disasters. Ulvan is the primarily component polysaccharide of the cell wall of Ulva and its complex structure and monosaccharide composition resulted in various biological activities. However, the high-value and effective utilization of extracted ulvan have been obstructed by limitations ranging from large molecular weight and low solubility to poor bioavailability. Ulva oligosaccharide obtained by degrading ulvan can not only ideally retain the various biological activities of ulvan very well but also effectively solve the problems of low solubility and poor bioavailability. The preparation and biological activity studies of ulvan and Ulva oligosaccharides have become a hot spot in the field of marine biological resources development research. At present, the comprehensive reviews of ulvan and Ulva oligosaccharides are still scarce. What are overviewed in this paper are the chemical composition, structure, extraction, and purification of ulvan and Ulva oligosaccharides, where research progress on the biological activities of ulvan and Ulva oligosaccharides is summarized and prospected. A theoretical and practical basis has been provided for further research on ulvan and Ulva oligosaccharides, as well as the high-value development and effective utilization of marine algae resources. Graphical Abstract